The Effect of Breathing Patterns Common to Competitive Swimming on Gas Exchange and Muscle Deoxygenation During Heavy-Intensity Fartlek Exercise - Grossman, Kevin J.; Lim, David J.; Murias, Juan M.; Belfry, Glen R. (Frontiers in Physiology, 2021)
During competitive freestyle swimming, the change of direction requires a turn followed by ∼15 m of underwater kicking at various intensities that require a ∼5 s breath-hold (BH). Upon surfacing, breathing must be regulated, as head rotation is necessary to facilitate the breath while completing the length of the pool (∼25 s). This study compared the respiratory and muscle deoxygenation responses of regulated breathing vs. free breathing, during these 25–5 s cycles. It was hypothesized that with the addition of a BH and sprint during heavy-intensity (HVY) exercise, oxygen uptake (VO2) and oxygen saturation (SatO2) would decrease, and muscle deoxygenation ([HHb]) and total hemoglobin ([Hbtot]) would increase. Ten healthy male participants (24 ± 3 years) performed 4–6 min trials of HVY cycling in the following conditions: (1) continuous free breathing (CONLD); (2) continuous with 5 s BH every 25 s (CONLD-BH); (3) Fartlek (FLK), a 5 s sprint followed by 25 s of HVY; and (4) a combined Fartlek and BH (FLK-BH). Continuous collection of VO2 and SatO2, [Hbtot], and [HHb] via breath-by-breath gas analysis and near-infrared spectroscopy (normalized to baseline) was performed. Breathing frequency and tidal volumes were matched between CONLD and CONLD-BH and between FLK and FLK-BH. As a result, VO2 was unchanged between CONLD (2.12 ± 0.35 L/min) and CONLD-BH (2.15 ± 0.42 L/min; p = 0.116) and between FLK (2.24 ± 0.40 L/min) and FLK-BH (2.20 ± 0.45 L/min; p = 0.861). SatO2 was higher in CONLD (63 ± 1.9%) than CONLD-BH (59 ± 3.3%; p < 0.001), but was unchanged between FLK (61 ± 2.2%) and FLK-BH (62 ± 3.1%; p = 0.462). Δ[Hbtot] is higher in CONLD (3.3 ± 1.6 μM) than CONLD-BH (-2.5 ± 1.2 μM; Δ177%; p < 0.001), but was unchanged between FLK (2.0 ± 1.6 μM) and FLK-BH (0.82 ± 1.4 μM; p = 0.979). Δ[HHb] was higher in CONLD (7.3 ± 1.8μM) than CONLD-BH (7.0 ± 2.0μM; Δ4%; p = 0.011) and lower in FLK (6.7 ± 1.8μM) compared to FLK-BH (8.7 ± 2.4 μM; p < 0.001). It is suggested that the unchanged VO2 between CONLD and CONLD-BH was supported by increased deoxygenation as reflected by decreased Δ[Hbtot] and blunted Δ[HHb], via apneic-driven redistribution of blood flow away from working muscles, which was reflected by the decreased SatO2. However, the preserved VO2 during FLK-BH vs. FLK has been underpinned by an increase in [HHb].